The Misfits : A Royal Conundrum - Book 1 - Yee, Lisa; Santat, Dan (New York : Random House, 2024)
An elite group of underdogs trained to fight crime must save their unique school from shutting down.
Keywords: Boarding schools -- Juvenile fiction; Schools -- Juvenile fiction; Friendship in children -- Juvenile fiction; Child detectives -- Juvenile fiction; Theft -- Juvenile fiction; Criminal investigation -- Juvenile fiction; Belonging (Social psychology) in children -- Juvenile fiction; Boarding schools -- Fiction; Schools -- Fiction; Friendship -- Fiction; Detectives -- Fiction; Stealing -- Fiction; Criminal investigation -- Fiction; Belonging -- Fiction; Mystery and detective stories; Detective and mystery fiction; School fiction; Action and adventure fiction